Impact of Narrative Exposure Therapy on torture survivors in the MENA region - Kirstine Viller Hansen, Ane; Sloth Hansen-Nord, Nete; Smeir, Issam; Engelkes-Heby, Lianne; Modvig, Jens (Torture Journal, 2018)
Introduction: Narrative Exposure Therapy (NET) is a brief cognitive-behavioural intervention for individuals with post-traumatic stress disorder (PTSD) which has mostly been used to treat traumatised asylum seekers and refugees in high-income settings. Evidence is scarce on the effectiveness of NET with torture survivors, especially in the Middle East and North African (MENA) region where health systems are unable to meet the increasing needs of mental health disorders caused by war and displacement. Click on pdf for full abstract.